EVALUASI TARIF BUS TERHADAP BIAYA OPERASIONAL BUS JURUSAN SAMARINDA-BONTANG - TOFA, MUS (KURVA S JURNAL MAHASISWA, 2016)
Freight rates are the results obtained from the users of its services seharus has been calculated in detail and adapted to the operational costs kendaraain itself. So it is important for actors to recalculate the service provider or detailing prior to the rates that have been enacted. Operational costs can not be separated from the service provider that the perpetrators be mandatory expenses for services provided to service users to be safe, comfortable and happy. service user satisfaction lies in the facility are met. The method used for the operational costs of data retrieval using the retrieval of primary and secondary, either directly into the field, and the data obtained from related fields. From the results of calculations it can be concluded that the tariffs have been determined with the vehicle operating costs. So that the perpetrators of the service provider could adjust tariffs on vehicle operating costs itself.